ChemInform Abstract: Facile Synthesis of Electrophilic Vinyl Boranes: Reactions of Alkynyl‐Borates and Diazonium Salts. Issue 5 (13th February 2013) - Zhao, Xiaoxi; Liang, Liyuan; Stephan, Douglas W.
Abstract The title reaction is thought to proceed via the interaction of the electron‐deficient cation derived from the diazonium salt (II) and the alkyne fragment of the alkynylborate (I) generating a transient carbocation adjacent the borate center.